On the Special Case of the Definiteness Effect: Conditions for the Admission of the Quantifier “every” into the Post-Copular Nominal Group of the English Existential Construction - O. V. Dolmatova (Научный диалог, 2019)
The reasons for the functioning of the quantifier “every” in the pivot noun phrases in English there-sentences are studied. The relevance of the study is seen in the incompleteness of the solution to the definiteness effect and its exceptions. The novelty of the study is due to the appeal to previously unexplored behavior of universal quantifiers in the desired construction. The sample included 626 examples of the breaking of the definiteness effect extracted from the British national corpus and the corpus of contemporary American English. It is stated that the quantifier “every” has specific conditions in this construction, subject to the principle of exhaustion of a set common to universal quantifiers. It is proposed to consider the emphatic meaning of the full involvement of the object, expressed as a noun in the main noun group, to be a characteristic feature. There are restrictions on the types of nouns that can occupy this position. The connection between the type of noun in the noun phrase and the connotation of the exhaustion of the set meaning is shown: the complete exhaustion of the species within the set, the complete involvement of the object as an indivisible unit, the complete exhaustion of the set consisting of separate countable elements. The role of actual and hyperbolized set boundaries is indicated. The conclusion about the normative nature of the certainty effect is drawn; cases of its breaking are considered as a variant of emphase.